Circulating levels of Interferon regulatory Factor-5 correlates with disease activity in Systemic Lupus Erythematosus Iraqi patients - Dahham, Zainab M.; Haddad, Namir I. A. (Journal of Contemporary Medical Sciences, 2022)
Objectives: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by a diversity of the phenotypes among the patients. SLE is still one of the great challenges due to the lacking of specific biomarkers for diagnosis, assessing disease activity, and prediction of response to therapy. This study aimed to investigate the role of circulating levels of IRF5 protein in sample of SLE Iraqi patients and its correlation with disease activity, to identify a potential immunological biomarker to mirror disease activity. Methods: Blood samples were taken from 59 participants diagnosed with SLE cases classified according to the American College of Rheumatology (ACR) criteria. They were scored through the SLE disease activity index 2000 (SLEDAI-2K) to estimate the disease activity, and according to it they were subdivided into “SLE-1 group” (SLEDAI-2k ≤5), and “SLE-2 group” (SLEDAI-2k >5), as well as age and gender matched healthy control group. Circulating levels of IRF5 protein were measured in sera samples by ELISA method. Results: Our result revealed that the circulating levels of IRF5 protein were significantly higher in the SLE-2 group rather than control group (p<0.01), while there was a non-significant difference between SLE-1 group and control group (p>0.05), as well as between both SLE patient groups. Moreover, the circulating IRF5 protein levels were found to be correlated positively and significantly with disease activity index in both SLE patient groups. The correlation between the circulating levels of IRF5 protein with other parameters revealed that a significant positive correlation was found in SLE-1 group with ESR and globulins, and negative correlation with Hb and (albumin/ globulin) ratio, while in SLE-2 group were positively correlated with urea, creatinine, and uric acid. The analysis of receiver operator curves (ROC) for circulating levels of IRF5 protein in SLE-1 and SLE-2 groups showed a good accuracy to distinguish SLE patients from healthy individuals (AUC=0.758, sensitivity=65.5%, and specificity=69%,), and (AUC=0.788, sensitivity=77.3%, and specificity=72.0%,), respectively. Conclusions: The circulating levels of IRF5 protein correlate with disease activity in SLE patients reflects the possibility of using it as a potential immunological biomarker for diagnosis, and monitoring the disease activity.